Predictors of acute stress disorder following a military maritime accident - Sanden, Sverre; Eid, Jarle; Hystad, Sigurd William (Frontiers in Psychiatry, 2025)
The present study examines the prevalence and predictors of symptoms of acute stress disorder (ASD) in crew members of Norwegian frigate HNoMS Helge Ingstad (n = 118) following the November 8th, 2018, collision with civilian oil tanker Sola TS, which led to grounding and total loss of the frigate. Collected six months prior to the accident (T1), pre-deployment scores on the General Health Questionnaire (GHQ-12), Hopkins Symptom Checklist 25 (HSCL-25) depression items, HSCL-25 anxiety items and professional self-efficacy were examined as predictors of scores on the Acute Stress Disorder Scale (ASDS) measured three weeks post-accident (T2), along with sex, personnel category, operational experience, and peri-traumatic perceived control and perceived coping, also collected at T2. Results show 28% of participants obtained scores indicating clinically significant symptoms of ASD. Baseline HSCL-25 anxiety, HSCL-25 depression and female sex were positively related to ASDS scores. Perceived control in the situation was negatively related to ASDS scores. Other factors were not predictive. Findings demonstrate that even slight elevations in pre-incident scores on symptoms of anxiety and depression increase risk for significant symptoms of ASD in military populations and suggest pre-deployment screening could help identify subgroups at higher risk of developing ASD after maritime accidents.